Plasma Triggered Grain Coalescence for Self-Assembly of 3D Nanostructures - Dai, Chunhui; Joung, Daeha; Cho, Jeong-Hyun (Nano-Micro Letters, 2017)
Grain coalescence has been applied in many areas of nanofabrication technology, including modification of thin-film properties, nanowelding, and self-assembly of nanostructures. However, very few systematic studies of self-assembly using the grain coalescence, especially for three-dimensional (3D) nanostructures, exist at present. Here, we investigate the mechanism of plasma triggered grain coalescence to achieve the precise control of nanoscale phase and morphology of the grain coalescence induced by exothermic energy. Exothermic energy is generated through etching a silicon substrate via application of plasma. By tuning the plasma power and the flow rates of reactive gases, different etching rates and profiles can be achieved, resulting in various morphologies of grain coalescence. Balancing the isotropic/anisotropic substrate etching profile and the etching rate makes it possible to simultaneously release 2D nanostructures from the substrate and induce enough surface tension force, generated by grain coalescence, to form 3D nanostructures. Diverse morphologies of 3D nanostructures have been obtained by the grain coalescence, and a strategy to achieve self-assembly, resulting in desired 3D nanostructures, has been proposed and demonstrated. Highlights: 1 Nanoscale grain coalescence induced during a Si etching process in a plasma etching system is characterized for self-assembly of 3D structures. 2 During the etching process, balancing the isotropic/anisotropic substrate etching profile and the etching rate make it possible to simultaneously release 2D nanostructures from the substrate and induce enough surface tension force, generated by grain coalescence, to form 3D nanostructures.